Positive lightning flashes recorded on the Säntis tower from May 2010 to January 2012. Issue 23 (5th December 2013) - Romero, Carlos; Rachidi, Farhad; Rubinstein, Marcos; Paolone, Mario; Rakov, Vladimir A.; Pavanello, Davide
Abstract [1] We analyze currents of 30 positive flashes recorded on the Säntis tower, Switzerland, from May 2010 to January 2012. The currents were classified into two types. Type 1 events exhibit a large, unipolar main pulse with a risetime of tens of microseconds, followed by subsidiary peaks separated by millisecond‐scale intervals. The main pulse in three flashes was preceded by a slowly rising ramp lasting several milliseconds and was followed by a relatively steady current with superimposed positive and negative pulses, constituting the first direct evidence of M components of both polarities. In four of the five type 1 flashes, the main current was preceded by pulse bursts, presumably due to attempted negative leaders. Type 2 events are characterized by a millisecond‐scale waveform with large, oscillatory pulse trains on its rising portion. These pulse trains are inferred to be due to upward negative stepped leaders. Peak currents of type 2 flashes are associated with the fast pulses. Our positive flashes of both types have a median peak current of 11.1 kA and a median duration of 80 ms, consistent with data recorded in Austria. Our measured median transferred charges are about 6 times larger than those at Switzerland's Monte San Salvatore and in Japan and about 3 times larger than in Austria. Eight type 2 flashes in our data set transported over 500 C of positive charge to ground. Our five type 1 events appear to be similar (except for the pulse duration) to their counterparts examined by Berger et al. (1975). Our type 2 events are "classical" upward flashes.